Monitoring aspects in EIA reports - Rahman, Md. Mizanur; Daud, Mohammed; Bardaie, Mohd Zohadie; Hassan, Mohd Nasir (Universiti Putra Malaysia, 1999)
As per the Environmental Impact Assessment Order, 1987, Malaysia, during the E.I.A study, monitoring plan needs to be proposed based on the significance of the predicted potential environmental impacts. This study reviewed monitoring aspects of 50 EIA reports prepared on several prescribed activities in Malaysia. Results showed that monitoring aspects are neither properly documented nor addressed in detail. Amongst the different environmental components, monitoring of Biological and Socio-economic aspects have not been given adequate attention. Although monitoring of air and water quality are given relatively more attention, still more than 33% of the EIA reports did not propose any monitoring plan for these two vital environmental aspects. In the case of noise impacts, more than 50% of the reports did not mention about monitoring of noise. Thus, for the better environmental management of the project as well as to provide the database for environmental impact predictions in future project planning, monitoring aspects should be properly documented and addressed in detail in the EIA reports with respect to the selection of environmental parameters, frequency of monitoring, and administration of the monitored database etc.